Excess of Plasma Cells with Pseudo-Gaucher Cells in a Case of Tuberculosis - A Case Report (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2013)
This report describes a case of 50 year old woman fever and bony pains with lytic lesion in skull. A polyclonal band was seen in γregion on serum electrophoresis. Bone marrow examination showed excess of plasma cells along with many Pseudo- Gaucher cells. The diagnosis of chronic inflammatory reaction was made. Although stain for AFB was negative, the patient responded to antitubercular treatment. The presence of pseudo-gaucher cells along with plasmacytosis is a rare finding in tuberculosis. SAARC Journal of Tuberculosis, Lung Diseases & HIV/AIDS; 2012; IX(2) 30-32 DOI: http://dx.doi.org/10.3126/saarctb.v9i2.7976